2010
DOI: 10.1038/nn.2699
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal photoperiod imprints the circadian clock

Abstract: Using real-time gene expression imaging and behavioral analysis, we found that perinatal photoperiod has lasting effects on the circadian rhythms expressed by clock neurons as well as on mouse behavior, and sets the responsiveness of the biological clock to subsequent changes in photoperiod. These developmental gene x environment interactions tune circadian clock responses to subsequent seasonal photoperiods and may contribute to the influence of season on neurobehavioral disorders in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
119
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 15 publications
12
119
1
Order By: Relevance
“…The current findings indirectly support the hypothesis that early life exposure to light may affect the long-term adaptive responses of the circadian system (Erren et al, 2011;Ciarleglio et al, 2011;Brooks and Canal, 2013). We previously found that the greater the springtime increase in solar insolation at the onset location, the younger the age of onset of bipolar disorder, especially for those with a family history of mood disorders.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The current findings indirectly support the hypothesis that early life exposure to light may affect the long-term adaptive responses of the circadian system (Erren et al, 2011;Ciarleglio et al, 2011;Brooks and Canal, 2013). We previously found that the greater the springtime increase in solar insolation at the onset location, the younger the age of onset of bipolar disorder, especially for those with a family history of mood disorders.…”
Section: Discussionsupporting
confidence: 87%
“…It was postulated that exposure to light during early life imprints an individual's circadian clock, setting vulnerability to future environmental challenges to the circadian system (Ciarleglio et al, 2011;Erren et al, 2011). We previously found that the larger the springtime increase in solar insolation at the onset location, the younger the age of onset of bipolar I disorder, especially for those with a family history of mood disorders (Bauer et al, 2012;Bauer et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, it is well known that photoperiodic information can be transmitted in utero via maternal melatonin secretion, and this prenatal signal can affect postnatal photoperiodic responses (Horton 1985, Stetson et al 1986, Lee et al 1987, Weaver et al 1987, Elliott & Goldman 1989) and the reproductive development of young (Prendergast et al 2000, Kauffman & Zucker 2002, Tuthill et al 2005. More recent studies have shown that perinatal photoperiod can have lasting effects on circadian rhythms expressed by clock neurons, wheel-running behavior (Ciarleglio et al 2011), depressive-and anxiety-like behaviors , and immune responses (Weil et al 2006). Finally, pilot studies in our laboratory of very young (3-week-old) hamsters gestated and held in LD or SD have demonstrated photoperiod-dependent changes in ovarian gene expression in the absence of morphological or histological differences.…”
Section: Gonadotropin Suppression In Ldsmentioning
confidence: 99%
“…The annual shortening of the photoperiod is believed to be the main factor in SAD onset; however, responses to cold temperatures and epigenetic changes have been documented in seasonal mammals and exhibit evolutionary conservation down to lower forms of life [3][4][5][6] , suggesting that many very basic physiologic mechanisms could contribute to SAD. Ultimately, SAD is a complex disease with both chronobiological and neurobiological underpinnings [7][8][9][10][11] , which may include an etiology that for some could even begin in utero [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%